Future Internet payment systems for business-to-consumer electronic commerce. - Chung, Virginie Tak Mew. (2008)
This research studies current and potential IPSs, their future outlooks, and what essentially makes up a successful IPS. It concludes that credit card will still dominate internet payment method in the foreseeable future. The study identifies 12 attributes of an ideal IPS and noted that e-barter is unlikely to take off in e-commerce.